Serum endocan levels in fresh IVF/ICSI cycles in women with endometriosis: a comparative prospective study - Mehmet Ufuk Ceran; Nafiye Yilmaz; Eser Colak; Nilufer Bayraktar; Yusuf Aytac Tohma; Hulusi Bulent Zeyneloglu (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: The current study tested the level of endocan, which is thought to have an effective role in both endothelial dysfunction and inflammation, in infertile women with endometriosis treated with in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). It is based on the hypothesis of chronic inflammation in the pathophysiology of endometriosis. Methods: This prospective case–control study included a total of 64 women who were in the IVF/ICSI program. The women were divided into two groups: endometriosis (n = 32) and non-endometriosis (n = 32). Their baseline characteristics, stimulation parameters, and IVF/ICSI outcomes (clinical pregnancy and live birth rates) were recorded. Blood samples collected at the beginning of the IVF cycle for endocan levels were analyzed with a sandwich enzyme immunoassay and the results were documented. Results: The endocan levels in the endometriosis group were significantly higher than those in the non-endometriosis group, i.e., 5010 pg/mL and 2738 pg/mL, respectively (p < 0.05). A significant weakly positive correlation was found between endocan levels and the presence of endometriosis (p < 0.05, r: 0.284). The cut-off value for endometriosis was determined as 4693 pg/mL with a sensitivity of 53.13% and a specificity of 78.12%. Clinical pregnancy was insignificantly higher in the non-endometriosis group (p = 0.079). However, live birth rates were significantly higher in the non-endometriosis group (p < 0.05). No correlation was found between clinical pregnancy and live birth rate and endocan levels (p > 0.05). Conclusion: High endocan levels were detected in women who underwent IVF/ICSI treatment for endometriosis and infertility and there was a positive correlation between them. However, there was no relationship between endocan levels and IVF/ICSI outcomes.